Hospital Accreditation Surveyors\' Evaluation Criteria in Iran - Ebrahim Jaafaripooyan; Ali Mohammad Mosadeghrad; Abbas Salarvand (Tehran University of Medical Sciences, 2019)
Background and Aim: Hospital accreditation is an external evaluation strategy used to improve the quality and effectiveness of services. Accreditation surveyors are among the important factors affecting the validity of accreditation results. Since the effectiveness of an accreditation system depends on its surveyors, the aim of this study is to identify the evaluation criteria of hospital accreditation surveyors in Iran. Materials and Methods: This qualitative study was conducted in 2017 based on stakeholders' views about the hospital accreditation program. Data were collected through semi-structured interviews and analyzed by thematic analysis method. Then the framework was designed and finalized with expert opinion. Results: Forty-four criteria identified for the evaluation of hospital accreditation surveyors in Iran were classified into six domains: personality, experience, knowledge, attitude, skills, and organizational citizenship behavior. Accreditation surveyors should have an acceptable combination of such criteria. Conclusion: Evaluation of accreditation surveyors with these criteria will lead to their better performance and ultimately promote the validity of the accreditation results. These criteria also result in a native definition for "accreditation surveyor" that can be used by the directors of accreditation system of hospitals for the management of accreditation surveyors.